Almada: The Other Margin - Santiago Baptista, Luis; Oliveira, Susana (Writingplace, 2023)
Almada, which is both a city and a county located on the south bank of the Tagus River and part of the Lisbon metropolitan area, has a unique identity that is influenced by both its proximity to and separation from Lisbon. This so-called ‘other margin’ was built on the productive base of the agricultural and fishing industries, the military and quarantine infrastructure, the burgeoning tourist industry on the Atlantic waterfront, the significant naval shipyard presence on the riverfront, the communal associations and cooperatives in the towns, and the expanding suburban condition throughout the entire territory. Almada is depicted here from various angles using various ways of representing its people, places, events and narratives that were taken from literary, artistic, architectural and documentary sources like books, illustrations, models, photos and movies. The urban narratives of Almada are replayed, alternating back and forth between past and present, memories and reality, the written and the visual.